2016
DOI: 10.1002/ecs2.1321
|View full text |Cite
|
Sign up to set email alerts
|

Modeling lake trophic state: a random forest approach

Abstract: Productivity of lentic ecosystems is well studied, and it is widely accepted that as nutrient inputs increase, productivity increases and lakes transition from lower trophic state (e.g., oligotrophic) to higher trophic states (e.g., eutrophic). These broad trophic state classifications are good predictors of ecosystem condition, services (e.g., recreation and esthetics), and disservices (e.g., harmful algal blooms). While the relationship between nutrients and trophic state provides reliable predictions, it re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 44 publications
3
42
0
2
Order By: Relevance
“…Moreover, recent studies have shown that RF models predict spatial patterns in river characteristics better than other more conventional methods [e.g., Booker and Snelder , ]. The RF technique has been previously applied in water resource studies to predict spatial patterns of different ecosystem components such as river bed surface grain size [ Snelder et al ., ], biotic indices [ Álvarez‐Cabria et al ., ], and lake trophic state [ Hollister et al ., ], among others.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, recent studies have shown that RF models predict spatial patterns in river characteristics better than other more conventional methods [e.g., Booker and Snelder , ]. The RF technique has been previously applied in water resource studies to predict spatial patterns of different ecosystem components such as river bed surface grain size [ Snelder et al ., ], biotic indices [ Álvarez‐Cabria et al ., ], and lake trophic state [ Hollister et al ., ], among others.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, RF provides two importance ranking indices, "mean decrease Gini" and "mean decrease accuracy" (also termed percent increase in mean square error (MSE)) [58]. The higher the MSE percentage, the greater the importance of the independent variable considered [59]. These indices can be applied to reveal the sensitivity of the model to input variables and to help decrease uncertainty.…”
Section: Random Forest (Rf)mentioning
confidence: 99%
“…The variable importance assessment in this study was conducted using the RF model. As one of its main benefits, RF can estimate the importance of predictor variables applied in the modeling process using the index percentage increase in mean square error (PIMSE) [59,71]. Table 6 shows the importance of predictor variables in predicting groundwater potential.…”
Section: Importance Analysis Of Predictive Factorsmentioning
confidence: 99%
“…While readily available spatial data coverages empower users across all levels of research and governance, they must be used with some caution in specific applications. In studies of lakes throughout the U.S., for example, lake‐specific variables are known to produce significantly improved predictive models of water quality and trophic state than models based on nationally‐available spatial covariates alone (Read et al ., ; Hollister et al ., ). Thus, while national databases enable prediction of response variables in lakes lacking in situ data, these predictions can be greatly improved with additional data not currently available nationally.…”
Section: Introductionmentioning
confidence: 99%